2015
DOI: 10.1007/s00330-015-3938-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of early gastric cancer with ulceration and resectable advanced gastric cancer using multiphasic dynamic multidetector CT

Abstract: • Early gastric cancer with ulceration and advanced gastric cancer have similar endoscopic appearances. • EGC-U shows significantly lower attenuation values in both arterial and portal phases. • Multiphasic dynamic contrast-enhanced MDCT differentiates EGC-U from AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The enhancement characteristics of GCAs have been a subject of interest in previous studies with implications on tumour detection and staging, and with reported differences among the histological categories[ 6 - 11 , 15 - 18 ]. Undifferentiated GCAs carry a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement characteristics of GCAs have been a subject of interest in previous studies with implications on tumour detection and staging, and with reported differences among the histological categories[ 6 - 11 , 15 - 18 ]. Undifferentiated GCAs carry a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to differentiate histological types of GCA using computed tomography (CT) [ 6 - 11 ]. Tsurumaru et al .…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of all measurements was evaluated using the ICC with 95% CIs model (3, k) for the intra-rater and model (2, k) for the inter-rater reliability ( 20 ) . The interpretation for the ICC with 95% CI was as follows: ≤0.20 poor, 0.21–0.40 fair, 0.41–0.60 moderate, 0.61–0.80 good, and 0.81–1.00 excellent ( 21 ) . Using the SPSS, the ICC model (2, k) was computed by selecting the options including two-way random, average measure, and absolute agreement.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that CT subjective findings (e.g., gastric wall thickness and enhancement pattern) play an important role in diagnosing gastric malignancies ( 7 ). However, distinguishing Borrmann type IV GC and PGL in lesion distribution, irregular gastric wall thickness and enhancement pattern, and so on is difficult with CT ( 8 ). Thus, an effective method is needed to differentiate Borrmann type IV GC and PGL.…”
Section: Introductionmentioning
confidence: 99%